2018
DOI: 10.32598/hdq.3.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cognitive Emotion Regulation and Meaning in Life With Health Anxiety Among Emergency Nurses

Abstract: The current study aimed to investigate the relationship of cognitive emotion regulation and meaning in life with health anxiety in nurses working in emergency department. Materials and Methods: It was a descriptive research in the form of correlation and prediction. The sample included 100 emergency nurses in Sari City, Iran selected by randomized method of sampling. The participants completed items of the Cognitive Emotion Regulation Questionnaire (CERQ), the Meaning in Life Questionnaire (MLQ) and health anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The results showed that occupational accidents have a positive and direct effect on work-family conflict. These results are in line with the findings of Pereira et al [22], Osca and Lopez [23], Malakoutikhah et al [24], and Jamshidian et al [25]. Occupational accidents lead to mental imbalance and psychological trauma in nurses, and this stress can be drawn in the process of the mechanism of transfer to the work-family environment.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that occupational accidents have a positive and direct effect on work-family conflict. These results are in line with the findings of Pereira et al [22], Osca and Lopez [23], Malakoutikhah et al [24], and Jamshidian et al [25]. Occupational accidents lead to mental imbalance and psychological trauma in nurses, and this stress can be drawn in the process of the mechanism of transfer to the work-family environment.…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that emergencies and their associated social emotions, especially the interweaving and collision of various negative emotions, have a great effect on public health [1,2]. During emergencies, positive psychological suggestion will make positive emotions generate, so as to avoid the influence caused by negative emotion, which is of a great help in controlling disease and restoring healthy life [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Chinese study found that one-sixth of health personnel suffered from psychological problems amid the outbreak of COVID-19, of whom only 35% sought treatment (Liu, Han et al 2020), nurses working in ICUs at baseline experience difficult working conditions and heavy responsibilities such as long and continuous care of critically ill and dying patients. Consequently, these nurses are exposed to the highest levels of stress during this pandemic (Jamshidian, Kiani et al 2018). In one study, the prevalence of anxiety in nurses caring of COVID-19 patients in ICUs was reported as 17.6% (Liu, Han et al 2020).…”
mentioning
confidence: 99%
“…Beside these, the nurses working in ICUs are at higher risk of being infected with COVID-19 due to a more special working environment and working with more severely ill patients who are under mechanical ventilation and require conducting dangerous and invasive procedures such as suctioning airways secretions and oral cavity, that increase the risk of transmission of COVID-19. (Millar 2020;Pappa, Ntella et al 2020;Shanafelt, Ripp et al 2020).Health anxiety is one of the important factors contributing to the higher levels of stress in ICU nurses (Jamshidian, Kiani et al 2018). Health anxiety is a cognitive disorder caused by misconceptions about disease symptoms and physical manifestations resulting from a person's beliefs about his/her illness or health (Fergus, Kelley et al 2016;Jamshidian, Kiani et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation